2019
DOI: 10.3390/ijgi8060253
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Web GIS Approach for Citizen Participation on Urban Evolution

Abstract: Web-mapping has been widely used to facilitate citizen participation in smart cities. Web-mapping has evolved from 2D static maps towards more dynamic and immersive 3D worlds such as virtual globes and scenes. Although current technologies allow us to build multidimensional representations, there is still a lack of research studies on how to further leverage them to foster citizen participation. Information on space–time changes can be an important asset for a successful citizen participation process. Citizens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
0
18
0
2
Order By: Relevance
“…In practice, this could be realized via the integration of the analysis tool with the existing 3D city model application development platforms, such as CesiumJS [75]. This way, the view analysis could become a complementary tool for processes that currently leverage the 3D city models on these platforms, such as participatory urban planning [76,77]. Finally, as the open data sets get richer, e.g., in terms of 3D green infrastructure data [78], the CityGML based urban view analyses could be utilized up to their full potential.…”
Section: Future Research Topicsmentioning
confidence: 99%
“…In practice, this could be realized via the integration of the analysis tool with the existing 3D city model application development platforms, such as CesiumJS [75]. This way, the view analysis could become a complementary tool for processes that currently leverage the 3D city models on these platforms, such as participatory urban planning [76,77]. Finally, as the open data sets get richer, e.g., in terms of 3D green infrastructure data [78], the CityGML based urban view analyses could be utilized up to their full potential.…”
Section: Future Research Topicsmentioning
confidence: 99%
“…Participatory GIS (PGIS), therefore, was then proposed to bridge the gap between participatory planning and GIS using a simplified graphical user interface (GUI) [28]. The advancement of web-based GIS is leading PGIS implementation in a web-based framework (Web-PGIS), allowing even more nonprofessionals to participate in spatial planning processes and anonymously express their views [30,31].…”
Section: Related Technologiesmentioning
confidence: 99%
“…However, the 2D maps and images used in traditional GIS and web GIS are insufficient to provide the public with an intuitive visualization environment. Studies have shown that 3D visualization can facilitate public participation in planning (see, for example, Lovett, et al [24], Lafrance, et al [30], Howard and Gaborit [32] and Lloret et al [33]). Various 3D visualization technologies have been applied to support participation in spatial planning such as visual reality (VR) [27,34], Java 3D [35], virtual reality markup language (VRML) [36,37], the Extensible 3D (X3D) X3D [38], keyhole markup language (KML) [39], and virtual globe-based 3D online visualization [40].…”
Section: Related Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The last two papers on urban data provide a web GIS for handling and disseminating multidimensional data. The web GIS in [4] models the spatiotemporal evolution of a city in four dimensions. The platform provides dynamic 3D city models that are used to promote citizen participation by letting them visualize and assess different scenarios.…”
Section: Content Of the Issuementioning
confidence: 99%